Building materials: Influence of physical, mechanical and acoustic properties in sound prediction models. Issue 1 (March 2019) - Santoni, Andrea; Fausti, Patrizio; Bonfiglio, Paolo
Several models to compute the sound reduction index of a building partition, based on different approaches, can be found in the literature. Building construction involves a great variety of materials, and regardless of the chosen sound transmission simulation prediction approach, their elastic and physical properties, which are necessary as input data, have a strong influence on the accuracy of the predicted results. In this article, the influence of such properties is investigated, by means of a prediction model based on the method proposed by the recently updated standard EN ISO 12354. Moreover, the reliability of different prediction models and the consistency of their results have been tested, by simulating several building partitions made of various materials, both homogeneous and non-homogeneous.